PERSEPSI GENERASI MUDA TERHADAP PELESTARIAN TRADISI KUMPUL SANAK DI DESA BERINGIN LUBAI - Agusti, Abizar; Faisal, Emil El (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the perceptions of young people toward the preservation of the Kumpul Sanak tradition in Beringin Village, Lubai District, Muara Enim Regency. The research problem arises from social and cultural changes caused by modernization, which potentially influence the interest and involvement of the younger generation in maintaining local traditions. This study employed a qualitative approach using an ethnographic method to gain an in-depth understanding of the views, attitudes, and experiences of young people regarding the Kumpul Sanak tradition within the social and cultural context of the community. Data were collected through participatory observation, in-depth interviews, and documentation involving the village head, traditional leaders, religious leaders, and young people as research informants. The findings indicate that, in general, young people have a positive perception of the Kumpul Sanak tradition and view it as an important means of strengthening kinship ties, preserving cultural identity, and fostering social cohesion. However, several challenges in preserving the tradition were identified, including the influence of social media, the busy lifestyles of young people, and changes in social interaction patterns. Despite these challenges, the active participation of some young people demonstrates the potential sustainability of the Kumpul Sanak tradition, particularly when supported by families, community leaders, and the village government. This study is expected to contribute to efforts to preserve local traditions through the empowerment of the younger generation amid ongoing social change. Keywords: youth perception; cultural preservation; Kumpul Sanak tradition